Hats and headdresses. (Kent : Tick Tock, 2006)
Looks at the various kinds of hats and headdresses worn throughout history and how they have changed since ancient times.
6.0
3-6
Keywords: Headgear -- History -- Juvenile literature; Headgear -- History; Headgear -- History